2022
DOI: 10.3390/ijerph19095488
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Head Impacts and Acceleration Associated with Soccer

Abstract: Epidemiological studies of the neurological health of former professional soccer players are being undertaken to identify whether heading the ball is a risk factor for disease or premature death. A quantitative estimate of exposure to repeated sub-concussive head impacts would provide an opportunity to investigate possible exposure-response relationships. However, it is unclear how to formulate an appropriate exposure metric within the context of epidemiological studies. We have carried out a systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…However, the two studies vary in several key aspects. The current investigation had individuals successfully perform 40 headers with a 20-min span at a distance of ∼25 m, whereas Harriss et al (19), had players engage in just 5 headers, although these were performed in under a minute at a distance of just ∼8 m. Moreover, they propelled the ball at 21.6 km/h toward the participants, whereas the current protocol used initial velocity of 77.5 ± 3.7 km/h, resulting in average linear and rotational head accelerations near the upper values previously reported (54). Finally, the previous investigation examined spontaneous HRV and cardiac BRS measures in a supine position; whereas in this study they were taken in an upright position, which is known to reduce variation and enhance reproducibility (55).…”
Section: Comparison To Previous Researchmentioning
confidence: 74%
“…However, the two studies vary in several key aspects. The current investigation had individuals successfully perform 40 headers with a 20-min span at a distance of ∼25 m, whereas Harriss et al (19), had players engage in just 5 headers, although these were performed in under a minute at a distance of just ∼8 m. Moreover, they propelled the ball at 21.6 km/h toward the participants, whereas the current protocol used initial velocity of 77.5 ± 3.7 km/h, resulting in average linear and rotational head accelerations near the upper values previously reported (54). Finally, the previous investigation examined spontaneous HRV and cardiac BRS measures in a supine position; whereas in this study they were taken in an upright position, which is known to reduce variation and enhance reproducibility (55).…”
Section: Comparison To Previous Researchmentioning
confidence: 74%
“…However, stronger forms of impacts to the head -those associated with higher levels of acceleration compared to the heading 26 Overall, these findings suggest that there is little or no association between heading the ball and reduced cognitive function. This is consistent with the findings of some previous studies 10, 13,14 , recently summarised in a systematic review In our study, we used a questionnaire that was developed, piloted and validated in a group of former professional players.…”
Section: Discussionmentioning
confidence: 85%
“…We do not find a clear association between exposure to heading and cognitive function later in life. However, stronger forms of impacts to the head – those associated with higher levels of acceleration compared to the heading 26 – were found to be associated with poorer cognitive function, albeit among forwards only. Soccer-related concussions were found to be associated with poorer cognitive function later in life overall, and particularly among defenders and goalkeepers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous work suggested that male soccer players experience a greater number of RHI, but female soccer players experience higher amplitude RHI (21–23). A recent systematic review and meta-analysis suggested that the mean number of RHI from soccer heading per hour was 2.4 in male soccer players and 0.5 in female soccer players, whereas the mean amplitude of RHI was 15.9 g in female soccer players and 13.9 g in male soccer players (24).…”
mentioning
confidence: 99%